Upaya Ustadzah dalam Mengatasi Problematika Santri pada Proses Pembelajaran Mengaji Kitab Tajwid Yanbu’a Kelas Sifir C Putri di Pondok Pesantren Hidayatul Mubtadiin Jati Agung Lampung Selatan Tahun Ajaran 2024/2025 - Safitri, Helen; Habib, A.; Rahayuningsih, Sri (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to describe the efforts made by the ustadzah (female Islamic teacher) in overcoming the problems that arise during the process of learning the Tajwid Yanbu’a book in the Sifir C female class at Pondok Pesantren Hidayatul Mubtadiin. This research employs a qualitative approach, utilizing observation, interviews, and documentation as data collection techniques. The data were analyzed descriptively through three stages: data reduction, data presentation, and drawing conclusions. Based on the findings regarding the ustadzah’s efforts in addressing the challenges faced by students in the process of learning the Tajwid Yanbu’a book, it can be concluded that the ustadzah plays a highly central and strategic role in ensuring the success of the learning process using the Yanbu’a method, particularly in overcoming various obstacles encountered by the students. The ustadzah functions not only as a teacher who delivers the material in a varied and adaptive manner, but also as a mentor who personally and collectively guides students in dealing with learning difficulties, and as a motivator who fosters enthusiasm and self-confidence through psychological and spiritual approaches. These efforts are carried out by prioritizing appropriate methods, effective communication, and attention to the emotional and religious development of the students, thereby making the learning process more optimal despite challenges such as differences in students’ basic abilities, limited facilities, and the intensity of pesantren activities. With such a comprehensive role, the ustadzah has succeeded in creating a conducive and transformative learning atmosphere, which not only enhances the students’ Qur’anic reading skills with proper tajwid, but also shapes their character and personality holistically in accordance with Islamic educational values.